2019
DOI: 10.4251/wjgo.v11.i11.1081
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hybrid minimally invasive esophagectomy vs open esophagectomy for esophageal cancer: A meta-analysis

Abstract: BACKGROUNDThe first line treatment regimen for esophageal cancer is still surgical resection and the choice of surgical scheme depends on surgeon. Now the efficacy comparison of hybrid minimally invasive esophagectomy (HMIE) and open esophagectomy (OE) is still controversial.AIMTo compare the perioperative and postoperative outcomes of HMIE and OE in patients with esophageal cancer.METHODSPubMed, EMBASE, and Cochrane Library databases were searched for related articles. The odds ratio (OR) or standard mean dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…We confirm the result of numerous studies including the recent prospective randomized MIRO trial, that the cumulative incidence of major postoperative pulmonary complications, especially pneumonia is significantly higher after OE compared to LAE [21,22,24,29,30,34,41]. In comparison to these studies, we observed slightly higher rates of postoperative pneumonia, presumably because we used the minorly modified "Revised Uniform Pneumonia Score" by Weijs et al for the retrospective assessment of pneumonia [37].…”
Section: Discussionsupporting
confidence: 88%
“…We confirm the result of numerous studies including the recent prospective randomized MIRO trial, that the cumulative incidence of major postoperative pulmonary complications, especially pneumonia is significantly higher after OE compared to LAE [21,22,24,29,30,34,41]. In comparison to these studies, we observed slightly higher rates of postoperative pneumonia, presumably because we used the minorly modified "Revised Uniform Pneumonia Score" by Weijs et al for the retrospective assessment of pneumonia [37].…”
Section: Discussionsupporting
confidence: 88%
“…In a meta-analysis with a total of 2397 patients from 2019, Yang et al showed comparable results of HMIE and OE regarding the number of harvested lymphnodes [ 12 ]. This was also true for our study population, which not only showed similar numbers of harvested lymphnodes, but also almost the complete number of patients being R0-resected in both groups (OE 98%, HMIE 100%).…”
Section: Discussionmentioning
confidence: 99%
“…While some report lower rates for OE compared to HMIE, other studies also show appreciably higher rates of anastomotic leakages after OE compared to HMIE [ 6 , 13 ]. Finally, a 2019 meta-analysis by Yang et al, including 17 studies and 2397 patients, also showed no difference between HMIE and OE (OR 0.95, 95% CI 0.67–1.35) [ 12 ]. Our results go in line with the literature here, since in our study the difference between anastomotic leakage rates is not statistically significant ( p = 0.171).…”
Section: Discussionmentioning
confidence: 99%
“…A contemporary meta-analysis by Yang et al comparing minimally invasive/hybrid oesophagectomy with open oesophagectomy has demonstrated the decreased frequency of complications and in-hospital mortality occurring in minimally invasive compared with open esophagectomy, which is usually attributed to a decrease in pulmonary complications [ 26 ]. A 2019 systematic review and meta-analysis of 55 studies including over 14,000 patients demonstrates that minimally invasive and hybrid esophagectomy was associated with fewer medical and surgical complications with similar oncologic outcomes with associated 18% lower five-year all-cause mortality compared with open esophagectomy (HR: 0.82, 95% CI: 0.76-0.88) [ 26 ]. Although our study did not deal with the mortality rate associated with oesophagectomy procedures, our results show that patients with insulin-dependent diabetes undergoing hybrid procedures have a three-fold risk of medical, surgical, wound complications and anastomotic leak as compared to IDDM undergoing open oesophagectomies (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A contemporary meta-analysis by Yang et al comparing minimally invasive/hybrid oesophagectomy with open oesophagectomy has demonstrated the decreased frequency of complications and in-hospital mortality occurring in minimally invasive compared with open esophagectomy, which is usually attributed to a decrease in pulmonary complications [26]. A 2019 systematic review and meta-analysis of 55 studies including over 14,000 patients demonstrates that minimally invasive and hybrid esophagectomy was associated with fewer medical and surgical complications with similar oncologic outcomes with associated 18% lower five-year all-cause mortality compared with open esophagectomy (HR: 0.82, 95% CI: 0.76-0.88) [26]. Although our study did not deal with the mortality rate associated with oesophagectomy procedures, our results show that patients with insulin-dependent diabetes undergoing hybrid procedures have a threefold risk of medical, surgical, wound complications and anastomotic leak as compared to IDDM undergoing open oesophagectomies (Table 3).…”
Section: Discussionmentioning
confidence: 99%